Impact of Pre-Operative Nebulized Lidocaine–Dexmedetomidine Combination Versus Monotherapy on Incidence, Severity, and Patient Comfort Scores of Post-Operative Sore Throat: A Randomized Controlled Clinical Trial - Pratul; Masrata Gull; Abhishek (International Journal of Biomedical Innovations and Engineering, 2026)
Post-operative sore throat (POST) is a common issue after endotracheal intubation and can reduce patient comfort and hinder recovery. This randomized, double-blind clinical study investigated how effective pre-operative nebulized lidocaine, dexmedetomidine, and their combination are in minimizing POST. Eligible adult patients classified as ASA I–II and scheduled for elective surgery under general anesthesia were randomly assigned to three groups. Nebulization was administered 15–20 minutes before induction using standardized dosing and uniform anesthesia protocol. The primary outcome was incidence of POST within 24 hours. Secondary outcomes included severity grading, patient comfort scores, and associated airway complications. The combination group demonstrated a significantly lower incidence and severity of POST compared to monotherapy groups. Patient comfort scores were consistently improved with combination therapy. Airway-related complications, such as hoarseness and cough, were also reduced. Pre-operative nebulized lidocaine–dexmedetomidine appears to be an effective strategy for minimizing postoperative airway morbidity.
Keywords: Post-operative sore throat; Randomized Controlled Trial; airway morbidity; dexmedetomidine; endotracheal intubation; general anesthesia; lidocaine; nebulization; patient comfort score; pre-emptive analgesia